Edgar Alexander Mearns papers - Mearns, Edgar Alexander, 1856-1916.
Correspondence, reports, family papers, newspaper clippings, printed matter, and other papers relating primarily to Mearns's career as a naturalist and U.S. Army surgeon. Documents his activities as a collector of data on animal and plant life and his participation in the Smithsonian African Expedition led by Theodore Roosevelt in 1909. Includes correspondence with Roosevelt.
Library of Congress Prints and Photographs Division.
Naturalist and U.S. Army surgeon.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Roosevelt, Theodore, -- 1858-1919.; Roosevelt, Theodore, -- 1858-1919 -- Correspondence; Mearns family; United States. -- Army -- Medical care; Botany; Natural history; Scientific expeditions -- Africa; Zoology; Africa -- Description and travel; Africa -- Discovery and exploration; Army surgeons; Naturalists